Depression in HIV and HCV co-infected patients: a systematic review and meta-analysis. Issue 9 (21st October 2017) - Fialho, Renata; Pereira, Marco; Rusted, Jennifer; Whale, Richard
Abstract: The aim of this study was to carry out a systematic review and meta-analysis of the differences in the prevalence of depression and presence of depressive symptoms between HIV/HCV co-infection, HIV mono-infection, and hepatitis C virus (HCV) mono-infection. A systematic electronic search of bibliographic databases was performed to locate articles published from the earliest available online until December 2014. Outcomes of depression were based on clinical interviews and validated self-reported measures of depression/depressive symptoms. Of the 188 records initially screened, 29 articles were included in the descriptive systematic review and six were included in the meta-analysis. The meta-analytic results indicated that, as measured by self-reported measures of depression, HIV/HCV co-infected patients were significantly more likely to report depressive symptoms than either HIV (SMD = .24, 95% CI: .03–.46, p  = .02) or HCV mono-infected (SMD = .55, 95% CI: .17–.94, p  = .005) patients. The variability of the results of the reviewed studies, largely dependent on the samples' characteristics and the methods of assessment of depression, suggests that a clear interpretation of how depression outcomes are affected by the presence of HIV/HCV co-infection is still needed. Failing to diagnose depression or to early screen depressive symptoms may have a significant impact on patients' overall functioning and compromise treatments' outcomes.